SISTEM KONTROL PEMANAS AIR MENGGUNAKAN SENSOR ULTRASONIK DAN ARDUINO UNO - Shafira Afra; Nur Wahyudin; Reza Vahlevi; Hendry Prayoga; Novia Dwi Prasetyo (Power Elektronik : Jurnal Orang Elektro, 2020)
Abstract - A water heater control system is a device used to control water temperature by utilizing a heating element to heat water. By using a water heater control system, the heating element will activate when the water temperature is below the desired temperature and the heating element will automatically turn off when the temperature is above the desired temperature. To measure temperature in water, using a temperature sensor that is thermally sensitive resistor or commonly called thermocouple. The thermocouple resistance value will change with temperature changes. By using the principle of voltage divider, the voltage value will be input to Arduino and processed into temperature. To realize the water heating control system, a thermistor is needed as a temperature sensor, Arduino as an input processor, heating element as an actuator, and an LCD to display the temperature of the water. In addition, it is needed. [5]                    Relay that functions as an electrical switch, in controlling the water conditions contained in a box that is equipped with an ultrasonic sensor as a prediction of the distance of the water that has been programmed. So that water can flow automatically with a distance controller that has been determined, if the distance of the water with ultrasonic. To be able to see it requires a valve / or drain plug that can move to the right or left. To drive the valve using a DC motor as a drive, with a type of DC servo motor. Because the DC motor uses direct current that requires a voltage of 4-6 Volt DC, because DC servo motors only move the valve which is small in shape. DC servo motor is a motor that is able to work both ways (CW and CCW) with deflection of each angle reaching 90 ° so that the total deflection angle from right - center - left is 180 °. The magnetic field of a DC servo motor is generated by a permanent magnet of a servo motor, so there is no need for power to create a magnetic field                    Servo motor will work well if the control pin is given with a frequency of 50Hz. Where when the signal with a frequency of 50Hz is achieved at 1.5ms Ton duty cycle conditions, the rotor of the motor will stop right in the middle (0 ° / neutral angle). When the Ton duty cycle of a given signal is less than 1.5ms, the rotor will rotate to the left by forming an angle that is linear in magnitude of the Ton duty cycle, and will survive in that position.[6] Keywords - Arduino UNO, LCD, Thermocouple, Water Temperature, Rela, Motor Servo.